Policy Brief: Advancing Digital Agriculture in Ethiopia: Experiences and Achievements from the CGIAR and Partners - Ahmed, Jemal Seid; Degefie, Degefie Tibebe; Worku, Wuletawu Abera; Sotelo, Steven; Grossi, Amanda; Ghosh, Aniruddha; Ramirez Villegas, Julian Armando; Teferi, Demissie; Solomon, Dawit; Desta, Lulseged Tamene (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
This policy brief synthesizes the collective impacts, lessons, and policy pathways emerging from the Alliance of Bioversity and CIAT’s collaborative work to advance digital agriculture in Ethiopia through the AICCRA project and beyond. The country’s rapidly evolving digital ecosystem is demonstrating tangible benefits—from measurable increases in crop yields and farmer incomes to improved decision-making across institutions. Platforms such as the NextGen Fertilizer Advisory, EDACaP, AgDataHUB, and ASIS are strengthening productivity, climate resilience, and risk management while moving beyond pilot phases toward national scale. Drawing on these experiences, the brief distills key lessons highlighting that human-centered design, multi-stakeholder collaboration, continuous capacity building, and strong data governance are foundational to success. It underscores that technology alone is insufficient—digital tools must be embedded within inclusive, user-driven systems supported by enabling policies and sustainable financing. The brief concludes with actionable policy recommendations aligned with Ethiopia’s Digital Agriculture Roadmap (2025–2032), calling for investments in rural connectivity, digital literacy, interoperable data systems, and inclusive innovation models that ensure digital transformation in agriculture is both equitable and enduring